A novel MBTPS2 variant associated with BRESHECK syndrome impairs sterol‐regulated transcription and the endoplasmic reticulum stress response. Issue 2 (15th October 2021) - Strong, Alanna; March, Michael E.; Cardinale, Christopher J.; Kim, Sophia E.; Merves, Jamie; Whitworth, Hilary; Raffini, Leslie; Larosa, Christopher; Copelovitch, Lawrence; Hou, Cuiping; Slater, Diana; Vaccaro, Courtney; et al.
Abstract: Ichthyosis follicularis, atrichia, and photophobia syndrome (IFAP syndrome) is a rare, X‐linked disorder caused by pathogenic variants in membrane‐bound transcription factor protease, site 2 ( MBTPS2 ). Pathogenic MBTPS2 variants also cause BRESHECK syndrome, characterized by the IFAP triad plus intellectual disability and multiple congenital anomalies. Here we present a patient with ichthyosis, sparse hair, pulmonic stenosis, kidney dysplasia, hypospadias, growth failure, thrombocytopenia, anemia, bone marrow fibrosis, and chronic diarrhea found by research‐based exome sequencing to harbor a novel, maternally inherited MBTPS2 missense variant (c.766 G>A; (p.Val256Leu)). In vitro modeling supports variant pathogenicity, with impaired cell growth in cholesterol‐depleted media, attenuated activation of the sterol regulatory element‐binding protein pathway, and failure to activate the endoplasmic reticulum stress response pathway. Our case expands both the genetic and phenotypic spectrum of BRESHECK syndrome to include a novel MBTPS2 variant and cytopenias, bone marrow fibrosis, and chronic diarrhea.